Abused child syndrome with psychological and social implication - Leonor Ramírez Quesada; Meilyn Ricardo Ramírez; Augusto César Brooks Legeyre (Centro Provincial de Información de Ciencias Médicas, 2018)
Child abuse is an universal problem which has many causes that involve a great variety of biological psychological and social factors. It is all type of aggression of parents, family or other people to a child to punish or to damage him. It also includes the lack of care for his basic needs of feeding, housing, dressing, health, protection and affection, reason why in this work it is commented about the topic, and the traumatic experience lived by 2 children is exposed .